Les élites gouvernementales en Grèce, en Roumanie et en Espagne - Ekkehard W. Bornträger (Cahiers Balkaniques)
Our paper addresses some aspects of the present composition of ministerial elites in Greece, Romania and Spain by means of a comparative statistical approach comprising data on geographical origin, academic and professional background and gender distribution.